PRODUCTIVITY STATUS OF DADIN KOWA RIVER CONTINUUM, GOMBE STATE, NIGERIA - MUHAMMAD, KABIRU; KOTOS, A. ABUBAKAR; SULAIMAN, NAZEEF; GARKUWA, NURU ADAMU (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY (2536-6041), 2021)
Assessment of Physico-chemical parameters, occurrence and distribution of Aquatic biota in Dadin-Kowa River Contiuum Gombe State were carried out for a period of Eighteen month. Three sampling stations were chosen and standard methods and identification guide were used to determine physicochemical and biological parameters. Result of Physicochemical parameters showed that Temperature, pH, Alkalinity, Transparency and Conductivity ranged between 21 - 27oC, 6.3-7.8, 28.1-46.2mg/L, 48.5-76.7cm, 54.0- 397.5μs/cm respectively, while Dissolved oxygen concentration, Biochemical Oxygen Demand, Calcium, Magnesium, Hardness, Iron, Nitrate-Nitrogen, Phosphate-Phosphorus ranged between l.l-3.4mg/L, 2.2-39mg/L, 11.3-23.2mg/L, 4.5-8.9mg/L, 40.0-88.5mg/L, 0.1-3.3mg/L, 0.3-1.5mg/L, 0.3-2.0mg/L respectively. A total of sixteen (16) phytoplankton species were recorded of which four classes of algae were identified. These are chlorophyta (25.9%), cyanophyta (23.9%), bacillariophyta. (48.9%) and dinophyta (15. 7%).Three major classes of zooplankton were recorded rotifera (36.9%) cladocera (35.5%) and copepoda (27.4%). Distribution of planktons varied with the variation in the physico-chemical parameters. The findings of the study revealed that the water body of Dadin-Kowa was moderately polluted.